STUDI GENDER: JARINGAN SOSIAL PENGEMIS ANAK PEREMPUAN DI KOTA BUKITTINGGI - Yenita Yatim; Budi Juliardi (Universitas Islam Negeri Imam Bonjol Padang, 2016)
Beggar is part of the big city problem in Indonesia. Bukittinggi in West Sumatera was not immune from this problem, especially on the children who become beggar. These beggars have pattern of work that make up the social network. Descriptive qualitative research was employed in this study where it involve the children who become beggars. The aim is to explore the ponomenon and the types of social network among the girls beggar. The data of this reserarch are acquired from the girls who run her live as the beggar who are regularly settled and stay aroud the Jam Gadang clock Tower. Finally, this research conclude that the shape of a social network that is developed by child gepeng in Bukittinggi are: 1) sosial network based on kinship, 2) social network are formed by social groups in the pattern of vertical relationships, 3) social network are formed in new social groups in order to meet the needs of each.